STRUKTUR POPULASI BEKANTAN (NASALIS LARVATUS) DI RAWA GELAM - Reni Srimulyaningsih; Maiser Syaputra (Jurnal Belantara, 2021)
Number of proboscis monkey population in Cajuputi Swamp Forest is 258 individual. This population is strongly influenced by condition of its habitat which is to degradation to 3.417 hektar. The object of research is to analyzed structure of proboscis monkey population. Method of research are river survey (Sha et al, 2008) and concentration count (Anonymous, 1981; Alikodra, 2002). The avarage density of proboscis monkey in their homerange is 3 individuals/hectares, with 30,2% males and 48,5 % females. This population is slow growth because there is only one baby/year, this is also indicated by number of 14 individuals babies (5,4%) and 41 infant (15,9%) lower when compared to number of adult indiviuals, so it is very worryng for continued growth of the population.